PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL (CONTEXTUAL TEACHING AND LEARNING) DALAM MENGIDENTIFIKASI STRUKTUR DAN UNSUR KEBAHASAAN TEKS EKSPOSISI PADA SISWA KELAS X SMA NEGERI 1 PAGADEN - Irpan Maulana; Firky Raniansyah (STKIP Subang, 2023)
Contextual learning model (CTL) is one of the learning models in the 2013 Curriculum. The low interest in reading by students and the use of unsuitable learning models are behind this research. This study aims to determine the influence of contextual learning models (CTL) in identifying the structure and linguistic elements of exposition texts in Class X SMA Negeri 1 Pagaden students. Contextual learning model (CTL) is one of the learning models in the 2013 Curriculum. The low interest in reading by students and the use of unsuitable learning models are behind this research. This study aims to determine the influence of contextual learning models (CTL) in identifying the structure and linguistic elements of exposition texts in Class X SMA Negeri 1 Pagaden students. Contextual learning model (CTL) is one of the learning models in the 2013 Curriculum. The low interest in reading by students and the use of unsuitable learning models are behind this research. This study aims to determine the influence of contextual learning models (CTL) in identifying the structure and linguistic elements of exposition texts in Class X SMA Negeri 1 Pagaden students. Contextual learning model (CTL) is one of the learning models in the 2013 Curriculum. The low interest in reading by students and the use of unsuitable learning models are behind this research. This study aims to determine the influence of contextual learning models (CTL) in identifying the structure and linguistic elements of exposition texts in Class X SMA Negeri 1 Pagaden students. Contextual learning model (CTL) is one of the learning models in the 2013 Curriculum. The low interest in reading by students and the use of unsuitable learning models are behind this research. This study aims to determine the influence of contextual learning models (CTL) in identifying the structure and linguistic elements of exposition texts in Class X SMA Negeri 1 Pagaden students. Contextual learning model (CTL) is one of the learning models in the 2013 Curriculum. The low interest in reading by students and the use of unsuitable learning models are behind this research. This study aims to determine the influence of contextual learning models (CTL) in identifying the structure and linguistic elements of exposition texts in Class X SMA Negeri 1 Pagaden students. Contextual learning model (CTL) is one of the learning models in the 2013 Curriculum. The low interest in reading by students and the use of unsuitable learning models are behind this research. This study aims to determine the influence of contextual learning models (CTL) in identifying the structure and linguistic elements of exposition texts in Class X SMA Negeri 1 Pagaden students. Contextual learning model (CTL) is one of the learning models in the 2013 Curriculum. The low interest in reading by students and the use of unsuitable learning models are behind this research. This study aims to determine the influence of contextual learning models (CTL) in identifying the structure and linguistic elements of exposition texts in Class X SMA Negeri 1 Pagaden students.